The Association of Hypertension with Obesity and Metabolic Abnormalities among Chinese Children - Haiquan Xu; Xiaoqi Hu; Qian Zhang; Songming Du; Hongyun Fang; Ying Li; Jun Ma; Tingyu Li; Lin Du; Hongwei Guo; Guifa Xu; Ailing Liu (International Journal of Hypertension)
A total of 8898 Chinese children (4580 boys and 4318 girls) aged 7–13 years in 6 cities of east China were recruited. Data on height, weight, waist circumference, blood pressure, serum lipid profiles, glucose, and insulin were collected. The overall prevalence of hypertension was 11.1%. Overweight and obese children had a higher risk of developing hypertension than their counterparts (29.1%, 17.4%, and 7.8%, resp.) (P=0.0001). The means levels of triglycerides, glucose, insulin, and HOMA-IR (1.0 mmol/L, 4.5 mmol/L, 8.4 mU/mL and 1.7, resp.) among hypertensive children were all significantly higher than their normotensive counterparts (0.8 mmol/L, 4.5 mmol/L, 5.9 mU/mL, and 1.2, resp.) (P=0.0001). Compared with the healthy children, the risk (odds ratio, OR) of having hypertension among children with high triglycerides, hyperglycemia, and metabolic syndrome was 1.4 (95% confidence interval (CI): 1.0–2.0, P=0.0334), 1.5 (95% CI: 0.9–2.5, P=0.0890), and 2.8 (95%CI: 1.5–5.4, P=0.0014), respectively, after controlling for age, gender, BMI, income level, parents' education level and puberty. In conclusion, overweight and obese children have higher risk of having hypertension and children with dyslipidemia, hyperglycemia, and metabolic syndrome and higher HOMA-IR have higher risk of developing hypertension.